Research Trends on MoTrPAC and Exercise Science Applications - Minchul Lee (운동과학)
PURPOSE Exercise plays a crucial role in maintaining human health and is widely recognized for its effectiveness in preventing and managing chronic diseases. However, the molecular mechanisms by which exercise exerts its beneficial effects on the body remain unclear. The Molecular Transducers of Physical Activity Consortium (MoTrPAC) is a collaborative research initiative that brings together multiple institutions and organizations to investigate the molecular mechanisms of exercise. METHODS This article provides a comprehensive overview of the MoTrPAC, detailing its structure, research strategies, and methodologies. We reviewed the consortium's primary research objectives, methodologies, key findings, and potential applications in exercise science. This analysis was conducted through a systematic review of online databases and search engines, including PubMed, Web of Science, and Google Scholar. RESULTS The MoTrPAC uses animal models and human studies to explore the physiological effects of exercise on various tissues. Research by the consortium has demonstrated that different types and intensities of exercise induce specific gene expression changes, activate diverse metabolic pathways, such as fatty acid oxidation, glucose metabolism, and protein synthesis, and restructure protein interaction networks in muscle tissue. These studies have identified novel biomarkers that can be used to assess the molecular effects of exercise. CONCLUSIONS MoTrPAC significantly advances our understanding of the molecular mechanisms underlying the effects of exercise. The consortium's findings have the potential to inform the development of personalized exercise prescriptions and health management strategies. Future research should include more diverse populations and investigate the long-term effects of exercise to enhance our understanding of the profound impact of physical activity on human health.